Simultaneous reconstruction of tibial osteomyelitis-complicated soft tissue defects using free flap transplantation in conjunction with the masquelet technique: a retrospective study - Baobao Xue; Yubo Pan; Bingxuan Wang; Haifeng Dang; Tian Li; Chao Yang; Junjun Fan (BMC Musculoskeletal Disorders)
Abstract Objective To investigate the clinical effect of anterolateral femoral free flap combined with Masquelet technique in the treatment of tibial osteomyelitis with wound surface. Methods A retrospective study was conducted to analyze the clinical data of 25 patients with tibial osteomyelitis combined with defected wounds in Xijing Hospital of Fourth Military Medical University from Jun 2017 to Oct 2021. After one-stage treatment with free flap combined with Masquelet technique, the infection index, lower extremity function score (LEFS), and Mazur ankle function score were compared before bone defect repair and at the last follow-up. Results The anterolateral femoral free flaps of 25 patients in phase I survived. The healing time of bone fracture after stage II operation was 8–12 months [(7.2 ± 0.9) months]. At the last follow-up, the infection index was significantly lower than that before bone defect repair (P < 0.01). The LEFS and Mazur ankle function scores [(56.2 ± 7.9) and (78.2 ± 16.1)] of the affected limb were significantly higher than those before bone defect repair [(26.0 ± 8.6) and (44.7 ± 18.2)] (P < 0.01). Wounds of all patients’ legs healed well, without complications (foot drop, joint dysfunction, or deformity in the affected limbs). Conclusion The anterolateral femoral free flap combined with Masquelet technique is an effective treatment strategy for tibial osteomyelitis combined with soft tissue defects. This technology can effectively repair limb trauma, inhibit infection, and improve flexion and extension functions of knee and ankle joint.